2023
DOI: 10.1071/is23029
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary phylogeny for the pseudoscorpion family Garypinidae (Pseudoscorpiones: Garypinoidea), with new taxa and remarks on the Australasian fauna

Mark S. Harvey

Abstract: The pseudoscorpion family Garypinidae is globally distributed with 79 species in 21 genera and several species represented by Mesozoic and Eocene fossils. This was recently included with the family Larcidae in a unique superfamily, Garypinoidea but there are no phylogenetic hypotheses for the group. Sequence data were obtained for 14 species in 8 genera and numerous outgroup taxa that formed the basis for a preliminary molecular phylogeny. A new subfamily classification is proposed with Protogarypininae, subfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…There were less than 10 bats roosting in Mallory Cave in 2008 and 2009. Over 60 Townsend's big-eared bats were documented roosting in the cave in 2023(B. Stoner, personal communication, 20 March 2024. The cave was gated in 2011 which limited human disturbances to the bats and helped the bat colony increase in size.…”
Section: Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…There were less than 10 bats roosting in Mallory Cave in 2008 and 2009. Over 60 Townsend's big-eared bats were documented roosting in the cave in 2023(B. Stoner, personal communication, 20 March 2024. The cave was gated in 2011 which limited human disturbances to the bats and helped the bat colony increase in size.…”
Section: Ecologymentioning
confidence: 99%
“…A recent phylogenomic study found that Larcidae are sister to Garypinidae, and that they belong to their own superfamily, Garypinoidea, which in turn is sister to a larger clade of Cheiridioidea + Sternophoroidea + Cheliferoidea (Benavides et al 2019). A multi-gene analysis of larcids and garypinids found that Larca nested within Garypinidae (Harvey 2023).…”
Section: Introductionmentioning
confidence: 99%